Acceleration of postoperative recovery with brief intraoperative vagal nerve stimulation mediated via the autonomic mechanism - Maisiyiti, Alimujiang; Tian, Ming; Chen, Jiande D. Z. (Frontiers in Neuroscience, 2023)
Introduction Postoperative recovery is largely dependent on the restoration of gastrointestinal motility. The aim of this study was to investigate the effects and mechanisms of intraoperative vagus nerve stimulation (iVNS) on postoperative recovery from abdominal surgery in rats. Methods The Nissen fundoplication surgery was performed on two groups of rats: sham-iVNS group and iVNS group (VNS was performed during surgery). Animal’s behavior, eating, drinking and feces’ conditions were monitored at specific postoperative days. Gastric slow waves (GSWs) and electrocardiogram (ECG) were recorded; blood samples were collected for the assessment of inflammatory cytokines. Results (1) iVNS shortened initiate times to water and food intake (p = 0.004) and increased the number of fecal pellets (p < 0.05, vs. sham-iVNS) and the percentage of water content in fecal pellets (p < 0.05). (2) iVNS improved gastric pace-making activity at 6 h after surgery reflected as a higher percentage of normal slow waves (p = 0.015, vs. sham-iVNS). (3) iVNS suppressed inflammatory cytokines at 24 h after surgery compared to sham-iVNS (TNF-α: p = 0.001; IL-1β: p = 0.037; IL-6: p = 0.002). (4) iVNS increased vagal tone compared to sham-iVNS group at 6 h and 24 h after the surgery (p < 0.05). Increased vagal tone was correlated with a faster postoperative recovery to start water and food intake. Conclusion Brief iVNS accelerates postoperative recovery by ameliorating postoperative animal behaviors, improving gastrointestinal motility and inhibiting inflammatory cytokines mediated via the enhanced vagal tone.